Graham Greene and the Issue of Obsessive Love: The Critical Analysis of the End of the Affair - Alidou Razakou Ibourahima Boro (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Nowadays, human beings’ relationships take many forms. People are either parents, friends, colleagues, partners, lovers etc. As far as lovers are concerned, we sometimes observe excesses in their interactions. However, not everybody experiences love in the same way. Love, for some is joy, happiness while other people regard it as source of problems and sufferance. In Corneille’s Le Cid, Rodrigue and Chimène are paralyzed by love and suffering, while Romeo and Juliette get to the capital sacrifice for their intensive and polemical love affair in Shakespeare’s Romeo in Juliette.  This study aims at exploring the concept of obsessive love and its consequences through the characters of Graham Green’s The End of the Affair. To succeed in this study apart from books on the selected topic, I have used psychoanalysis as literary theory to access the issue. I examined the difference between obsessive love and true love. Of the results I came up with I can briefly say but a few that obsession can be destructive namely for the obsessed. It can also negatively affect the other members of the family tissue. Obsessive love unfortunately often replaces true love. Ways and means are suggested to cope with any sorts of love.